Análisis del uso del sistema UPAC en el crédito de vivienda, y su incidencia en la crisis de la década de los noventa en Colombia (2025)
The purpose of this research is to identify the causes and consequences of the financial crisis following the implementation of the use of the UPAC (Constant Purchasing Power Unit) system, from its implementation in 1972 to the evolution to the UVR system in 1999. Throughout the research, the characteristics of the creation of the UPAC system, its evaluation and the crisis generated by its link to inflation in the nineties are presented, as well as the effects generated by the crisis and the impact on the Colombian population. The economic and social situation of Colombia is briefly analyzed, highlighting the housing problems and the existing inflation conditions that motivated the creation of this mechanism. A theoretical framework based on theories of financial intermediation and indexation models, as well as Minsky's theory of financial instability, is used to interpret the dynamics of the UPAC system and its implications. The methodology includes statistical analysis of historical data and documentary review.